Alteration of Liver Biomarkers in Patients with SARS-CoV-2 (COVID-19) - Gholizadeh P; Safari R; Marofi P; Zeinalzadeh E; Pagliano P; Ganbarov K; Esposito S; Khodadadi E; Yousefi M; Samadi Kafil H (Dove Medical Press, 2020)
Pourya Gholizadeh,1,2 Rohollah Safari,3 Parham Marofi,4 Elham Zeinalzadeh,4 Pasquale Pagliano,5 Khudaverdi Ganbarov,6 Silvano Esposito,5 Ehsaneh Khodadadi,7 Mehdi Yousefi,8 Hossein Samadi Kafil7 1Student Research Committee, Tabriz University of Medical Sciences, Tabriz, Iran; 2Biotechnology Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 3Department of Microbiology, Imam Reza Hospital, Tabriz University of Medical Sciences, Tabriz, Iran; 4Hematology and Oncology Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 5Department of Medicine, University of Salerno, Salerno, Italy; 6Department of Microbiology, Baku State University, Baku, Republic of Azerbaijan; 7Drug Applied Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 8Stem Cell Research Center, Tabriz University of Medical Sciences, Tabriz, IranCorrespondence: Hossein Samadi Kafil Tel +98-9127184735Fax +98-4133364661Email Kafilhs@tbzmed.ac.irIntroduction: Coronavirus disease 2019 (COVID-19) emerged in China and spread worldwide. In this study, we assessed the characteristics of markers of the liver in patients with COVID-19 to provide new insights in improving clinical treatment.Patients and Methods: We recruited 279 patients who confirmed COVID-19 and the data of liver biomarkers and complete blood count of patients were defined as the day onset when the patients admitted to the hospital.Results: The average of LDH value was 621.29 U/L in all patients with COVID-19, and CPK was 286.90 U/L. The average AST was 44.03 U/L in all patients, and ALT was 31.14 U/L. The AST/ALT ratio was 1.64 in all patients. The measurement of CRP was increased by 79.93% in all patients. Average ALT and AST values of patients with elevated ALT were significantly increased in comparison to patients with normal ALT (P-value = 0.001), while AST/ALT ratio was significantly decreased compared to patients with normal ALT (P-value= 0.014). In addition, the average LDH of patients with elevated ALT was significantly increased compared to patients with normal ALT (P-value = 0.014).Conclusion: Hepatic injury and abnormal liver enzymes related to COVID-19 infection is an acute non-specific inflammation alteration.Keywords: SARS-CoV-2, COVID-19, hepatic injury, liver enzymes, aminotransferases